2003
DOI: 10.1007/s00280-003-0641-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wf-536, a novel ROCK inhibitor, against metastasis of B16 melanoma

Abstract: The results suggest that Wf-536 is a potentially valuable drug for preventing tumor metastasis both in monotherapy and in combination with an antineoplastic drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
55
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 16 publications
3
55
0
Order By: Relevance
“…The results of the present study revealed that afzelin inhibited the protein expression levels of MRCKα and ROCK1, clarifying that downregulation of LIMK1 by afzelin is due to its inhibitory effect on MRCKα and ROCK1, upstream in its signaling pathway. Previous studies have demonstrated that ROCK inhibitors appear to reduce the invasive ability of tumor cells in vitro and prevent the dissemination of tumor cells in vivo in different types of cancer, particularly in prostate cancer (10,(13)(14)(15)(16)(17)38). Furthermore, LIMK1, MRCKα and ROCK1 are proteins of interest in the development of novel cancer therapies due to their involvement in regulating actin organization (7) and, in combination with other proteins, maintaining the tight regulation of normal cell growth and differentiation (8,9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the present study revealed that afzelin inhibited the protein expression levels of MRCKα and ROCK1, clarifying that downregulation of LIMK1 by afzelin is due to its inhibitory effect on MRCKα and ROCK1, upstream in its signaling pathway. Previous studies have demonstrated that ROCK inhibitors appear to reduce the invasive ability of tumor cells in vitro and prevent the dissemination of tumor cells in vivo in different types of cancer, particularly in prostate cancer (10,(13)(14)(15)(16)(17)38). Furthermore, LIMK1, MRCKα and ROCK1 are proteins of interest in the development of novel cancer therapies due to their involvement in regulating actin organization (7) and, in combination with other proteins, maintaining the tight regulation of normal cell growth and differentiation (8,9).…”
Section: Discussionmentioning
confidence: 99%
“…The Rho GTPase myotonic dystrophy kinase-related Cdc42-binding kinase α (MRCKα), Rho-associated coiled-coil containing protein kinase (ROCK)1 and ROCK2 are responsible for the activation of LIMK1 (9,12). Previous studies have demonstrated the ability of ROCK inhibitors to reduce the invasive ability of tumor cells in vitro and prevent the spread of tumor cells in vivo, including melanoma and fibrosarcoma cells, as well as liver, breast, lung and prostate cancer tumor cells (13)(14)(15)(16)(17) Thus, inhibitors of LIMK1, MRCKα and ROCK1/2 are considered to restore normal cell proliferation and provide a key strategy for cancer treatment (18). Therefore, the aim of the present study was to evaluate the in vitro anti-prostate cancer activity of afzelin and its effect on prostate cancer-associated kinases.…”
Section: Introductionmentioning
confidence: 99%
“…Among these we should mention NCOA1 (nuclear receptor coactivator (1), a transcriptional coactivator belonging to the SRC family which is deregulated in breast and prostatic cancer and may potentiate gene expression by acting as a coactivator for nuclear hormone receptors and other transcription factors (TF) [44][45][46][47][48][49][50][51][52][53][54][55]; and ROCK2, a serine/threonine kinase member of the Rho pathway, involved in cell adhesion, migration, invasion, and mitosis [56][57][58][59], which may be a potential therapeutic target in human cancer cells and animal models [60][61][62][63][64][65][66][67][68].…”
Section: Discussionmentioning
confidence: 99%
“…There is a wealth of data implicating Rho GTPases in human cancer (Sahai and Marshall, 2002;Benitah et al, 2004) further suggesting that ROCK1 and ROCK2, as key mediators of Rho signaling, may have important roles (Narumiya et al, 2009). In support of this, preclinical studies have shown beneficial effects of ROCK inhibition on tumor incidence rates, volume, invasiveness and metastasis (Itoh et al, 1999;Somlyo et al, 2000;Nakajima et al, 2003;Ying et al, 2006;Ogawa et al, 2007;Xue et al, 2008). In addition, elevated ROCK1 and/or ROCK2 expression have been detected in several human cancers, which correlated with poor outcome (Kamai et al, 2002(Kamai et al, , 2003(Kamai et al, , 2004Abe et al, 2008).…”
mentioning
confidence: 97%